Literasi dan Inklusi Keuangan, serta Keterampilan Akuntansi untuk Keberlanjutan UMKM (Financial Literacy and Inclusion, as well as Accounting Skills for MSME Sustainability) - Dewi, Rachma Kusuma; Purwantini, Anissa Hakim (STIE Malangkucecwara, 2023)
This research analyzes the influence of financial literacy, financial inclusion, access to capital, financial technology and accounting skills on the sustainability of Micro, Small and Medium Enterprises (MSMEs) in Magelang City. The sample used was 333 MSMEs and analyzed using multiple regression with SPSS 25. The results of this study show that financial literacy, financial inclusion and accounting skills have a positive impact on the sustainability of MSMEs, while financial technology and access to capital do not have a significant impact. Internal company resources such as financial and accounting knowledge and capabilities are key factors in achieving sustainability for MSMEs